Evaluation of individualized para-tumor resection of cervical cancer patients based on three-dimensional reconstruction - Wang, Lu; Liu, Ping; Duan, Hui; Li, Pengfei; Li, Weili; Chen, Chunlin (Frontiers in Surgery, 2023)
Objective: To discuss the possibility of individualizing the para-tumor resection range (PRR) in cervical cancer patients based on three-dimensional (3D) reconstruction. Methods: We retrospectively included 374 cervical cancer patients who underwent abdominal radical hysterectomy. Preoperative computerized tomography (CT) or magnetic resonance imaging (MRI) data sets were collected to get 3D models. Postoperative specimens were measured to evaluate surgical scope. Oncological outcomes of patients with different depths of stromal invasion and PRR were compared. Results: A PRR of 32.35 mm was found to be the cut-off point. For the 171 patients with stromal invasion <1/2 depth, patients with a PRR over 32.35 mm had a lower risk of death and higher 5-year overall survival (OS) than that in the ≤ 32.35 mm group (HR=0.110, 95%CI: 0.012 to 0.988, P=0.046; OS: 98.8% vs. 86.8%, P=0.012). No significant differences were found in 5-year disease-free survival (DFS) between the two groups (92.2% vs. 84.4%, P=0.115). For the 178 cases with stromal invasion ≥1/2 depth, no significant differences were found in 5-year OS and DFS between groups (≤ 32.35 mm group vs. > 32.35 mm group, OS: 71.0% vs 83.0%, P=0.504; DFS: 65.7% vs 80.4%, P=0.305). Conclusion: In patients with stromal invasion < 1/2 depth, the PRR should reach 32.35 mm to get more survival benefit and in patients with stromal invasion ≥ 1/2 depth, the PRR should reach 32.35 mm at least to avoid worse prognosis. Cervical cancer patients with different depths of stromal invasion may receive tailoring resection of the cardinal ligament.